Reconstruction of Sakīnah Family Criteria During the Covid-19 Period - Andi Yaqub; Iswandi Iswandi; Jabal Nur (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This article describes the implementation and achievements of the sakīnah family during the Covid-19 period. Both refer to the technical guidelines of the Indonesian Ministry of Religious Affairs in 2011 regarding the criteria for the sakīnah family. This study uses sociological and al-maṣlaḥah approaches. The research location is in Konda District, Konawe Selatan Regency. The researchers obtained data from the Office of Religious Affairs (KUA), sub-district government, village heads, community leaders, and the public. This study found that the criteria for the sakīnah family were irrelevant to apply. The reason is that the expectations of these criteria are too high, especially in the fields of economy and social status. In addition, the KUA officers did not implement the sakīnah family counselling properly. Thus, the criteria for the sakīnah family need to be simplified and adapted to the conditions and characteristics of each region.